Trophic and spatial complementarity on seed dispersal services by birds, wild mammals, and cattle in a Mediterranean woodland pasture - Bueno, Rafael da Silveira [UNESP] (2021)
Most earth surfaces have undergone intensive land-use changes, creating habitat mosaics. Seed dispersal by animals is a crucial process in such mosaics, but community-wide studies comparing the functional complementarity and response to man-imposed habitat heterogeneity are rare. Here, we investigate the trophic and spatial seed dispersal networks underpinning a strong, woody vegetation expansion over a pastureland inside the largest forest remnant in western Sicily, Italy. Over two fruiting seasons, we surveyed transects in three distinct biomes within our study area: forest, pastureland, and unpaved road. In total, we collected 659 feces and tested for differences in defecation patterns and seed rain density of birds, wild mammals, and cattle. We also tested the degree of trophic and spatial specialization and modularity using a network approach. Overall, birds dispersed 1208 seeds/ha of nine plant species, including six exclusive. Mammals dispersed 679 seeds/ha from four wild species, three of which also dispersed by birds, and 38 seeds/ha of three cultivated species. In turn, mammals dispersed exclusively the seeds of wild pear (Pyrus amygdaliformis), the most abundant tree in the woodland pasture. Cattle only dispersed wild pear, but accounting for 56% of the dispersed seeds. Seed rain densities were significantly higher in woodland pastures than in forests. However, almost of half the seeds dispersed by cattle and red fox were deposited on unpaved roads. While both trophic and spatial networks were more specialized than expected, we did detect distinct modules. Our study demonstrated the magnitude of the effects of man-made habitat heterogeneity on seed dispersal services, giving baseline information for restoration programs as well as high nature value pastureland management strategies.